Perspective on the Design of a Knowledge-based System Embedding Linked Data for Process Planning. (2016) - Rehage, Gerald; Joppen, Robert; Gausemeier, Jürgen
Abstract: In simple terms, the Web of (Linked) Data is a distributed database with semantic facts about the world or any specific domain. The integration of Linked Data in knowledge-based systems (KBS) has the potential to reduce the maintenance effort for the underlying knowledge base. Using Linked Data in KBS leads to some new challenges that will be outlined in the paper. An important step during the design phase of the KBS is the comparison of the required knowledge and knowledge that is available as Linked Data. The required facts emerge from the problem-solving method and cover all facts that are necessary to conduct the intended decision. Whereas the available knowledge represent all relevant facts in internal and public Linked Data sets. Any remaining knowledge gap between required and available facts has to be closed primarily by rules and mash-ups to generate or transform the required facts automatically and keep everything up-to-date. This is one major step of the presented procedure and architecture to design a KBS based on Linked Data.